Factors Impacting Indonesian State-Owned Banks' Ability to Disburse Credit - Nuraeni, Natasya; Maryati, Mari (Program Studi Keuangan & Perbankan, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2024)
This study aims to determine the effect of non-performing loans (NPL) on credit distribution to Indonesian State-Owned Banks listed on the Indonesia Stock Exchange (IDX) from 2018 to 2022. Non-performing loans (NPL) were used in this study to measure the credit risk given by banks. The descriptive and quantitative research methods were used in this research. The data used is derived from secondary sources, specifically utilizing the financial report of each bank. The subject in this study is limited to each audited financial report of four Indonesian State-Owned Banks listed on the Indonesia Stock Exchange (IDX) from 2018 to 2022. The research result finds that Non-Performing Loans (NPL) did not have a significant impact on credit distribution in Indonesian State-Owned Banks listed on the Indonesia Stock Exchange (IDX) during the period of 2018 to 2022. This research provides an important contribution to understanding the dynamics of credit disbursing in Indonesian State-Owned Banks listed on the Indonesia Stock Exchange (IDX).